2016
DOI: 10.1016/j.socscimed.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

The impact of strengthening cigarette pack warnings: Systematic review of longitudinal observational studies

Abstract: Objectives Cigarette pack warnings are a tobacco control strategy used globally. To understand their impact, we systematically reviewed longitudinal observational studies examining national implementation of strengthened warnings. Methods We used comprehensive search procedures to identify observational studies examining the impact of strengthening cigarette pack warnings. We report longitudinal changes in knowledge, beliefs, attitudes, intentions, and behavior. Results We identified 32 studies conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
228
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 270 publications
(254 citation statements)
references
References 36 publications
15
228
2
1
Order By: Relevance
“…In Australia, 57% of smokers and 72% of recent quitters in 2008 reported that PWLs made them think about quitting and had helped them try to quit 58. A recent experimental study59 obtained an 18% ((40–34)/34) relative increase in quit attempts, and a meta-analysis obtained a 9% relative increase in quit attempts associated with PWLs 39…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…In Australia, 57% of smokers and 72% of recent quitters in 2008 reported that PWLs made them think about quitting and had helped them try to quit 58. A recent experimental study59 obtained an 18% ((40–34)/34) relative increase in quit attempts, and a meta-analysis obtained a 9% relative increase in quit attempts associated with PWLs 39…”
Section: Resultsmentioning
confidence: 98%
“…We reviewed evidence from diverse sources, including population-level and individual-level studies, data on trends in nations that have implemented PWLs and recent meta-analyses 39 40. Our best estimate of a 10% relative reduction in long-term smoking prevalence is lower than the 13% relative reduction obtained in a recent meta-analysis 39…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations